PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG, DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMENT YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Zakaria, Ilham Habibi; Santoso, Ferry; Hapsari, Ervina Ayu Dwi (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to determine the results of the effect of cash turnover, receivables turnover, inventory turnover on profitability in textile and garment sub-sector companies for the 2020-2022 period. This study has 22 textile and garment sub- sector companies with sampling techniques based on criteria using purposive sampling. The sample obtained based on the criteria of 20 companies per year. This type of research is quantitative. The data analysis technique used is quantitative with descriptive statistics using SPSS v.26. The results of this study state that partial cash turnover does not affect profitability, partial receivables turnover has a positive effect on profitability, and partial inventory turnover has a positive effect on profitability.